THE STUDENT OFFICERS’ VOCABULARY LEARNING STRATEGIES AND THEIR VOCABULARY TYPES MASTERY - Ellyana Ismayanti (Magister Scientiae, 2016)
This study investigates the student officers’ vocabulary strategies, vocabulary mastery types and their strategies tendencies. The type of maritime English vocabulary can be divided into academic and technical words type. The instruments used Schmitt’s taxonomy and maritime English vocabulary test. The result found that the students who used determination strategies were not able to master academic and technical words types. The students who used social strategies tended to master technical words type. Then, the students who used memory strategies tended to master technical words type. On the other hand, the students who used cognitive strategies tended to master academic words type. Meanwhile, the students who used metacognitive strategies tended to master two vocabulary types which consist of academic words and technical words.